Effect of Compression Garments in the Speed Performance among Track and Field and Swimming student-athletes in a Catholic University of the Philippines - Porto, Jerome A.; Alcantara, John Paul C.; Belaño, Jessiel Tanya L.; Bernal, Mae Andrea G.; Caballero, Ivana Dianne F.; Casao, Bryan Joshua R.; De Leon, Jose Martin L.; De Vera, Dustine Jorell T.; Porto, Analin E. (INSPIRETECH GLOBAL INSIGHT & DPE Universitas Pahlawan, 2023)
Background and Purpose: Speed is critical for sports such as swimming and track and field. One of the sports industry's solutions is compression garments to enhance athletic performance. This study aims to determine the effect of short and long compression garments on the speed performance of track and field and swimming athletes of the University of Santo Tomas. Methodology: The researchers used quantitative and experimental methods. This study focused on the athletes of the track and field and swimming teams of the University of Santo Tomas. The researchers conducted the study at the open field and swimming pool within the vicinity of the University; 14 athletes from track and field and 16 from the swimming team were invited to participate in the 60M Sprint Test and Critical Swim Speed Test. Results: The study shows a slight difference in the speed performance of track and field athletes when using short compression garments (7.54m/s) and long compression garments (7.44m/s). While swimming, the speed performance when using a long compression garment (1.450m/s) is higher than the short compression garment (1.512m/s). Both swimming (0.887) and track and field (0.559) show no significant difference in using the compression garment. Conclusion and Recommendations: Based on the study, there is a minimal difference in using long compression garments against short compression garments. Therefore, the researchers recommend using long compression garments since this garment slightly increases participants' speed which is vital in any sport measuring speed to win a race. The researchers recommend further study by increasing the number of participants, only endurance athletes participants, and including the materials used in making the garments. This further helps the claim that long and short compression garments affect speed performance regardless of sports or events.